Legal Protection For The Community In Cyber Space Through Regulation Forming With The Omnibus Method - Juaningsih, Imas Novita; Hidayat, Rayhan Naufaldi (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2022)
This study examines the laws and regulations in Indonesia that contain material related to cyberspace. The goal to be achieved is to provide a detailed description of the problems contained in laws and regulations, especially at the level of laws related to cyberspace, their implications in people's lives, and appropriate concepts to solve these problems. The method used is normative legal research with a state approach. The results of this study indicate that there is regulatory obesity that regulates cyberspace in Indonesia. There are 30 regulations at the statutory level. Moreover, the content material contained in it is still general in nature and has not been integrated with one another. This fact creates legal uncertainty in the realm of implementation, creating loopholes that can be exploited by irresponsible parties to carry out cyber crimes, such as the spread of negative content, cyber attacks, hacking and theft of personal data. The rise of crimes that occur in cyberspace is very detrimental to the wider community, disrupts security and public order, and even threatens the resilience of the state. Therefore, it is necessary to reform in the realm of law, namely by applying the omnibus method to draft universal sweeping laws that can integrate legal norms in many laws effectively and efficiently. ABSTRAK Penelitian ini mengkaji tentang peraturan perundang-undangan di Indonesia yang memuat materi terkait ruang siber. Tujuan yang hendak dicapai yaitu memberi gambaran secara detail mengenai problematika yang terdapat dalam peraturan perundang-undangan, terutama di tingkat undang-undang yang terkait dengan ruang siber, implikasinya dalam kehidupan masyarakat, dan konsep yang sesuai untuk menyelesaikan permasalahan tersebut. Metode yang digunakan ialah penelitian hukum normatif (normative legal research) dengan pendekatan undang-undang (statue approach). Hasil penelitian ini menunjukkan bahwa terjadi obesitas regulasi yang mengatur ruang siber di Indonesia. Regulasi tersebut berjumlah 30 di tingkat undang-undang. Terlebih, materi muatan yang terkandung di dalamnya masih bersifat general dan belum terintegrasi satu sama lain. Kenyataan yang demikian itu menimbulkan ketidakpastian hukum di ranah implementasi, sehingga menimbulkan celah yang dapat dieksploitasi oleh pihak-pihak yang tidak bertanggung jawab untuk melancarkan kejahatan siber, seperti penyebaran konten negatif, serangan siber, peretasan dan pencurian data pribadi. Maraknya kejahatan yang terjadi di ruang siber sangat merugikan masyarakat luas, mengganggu keamanan dan ketertiban umum, bahkan mengancam ketahanan negara. Oleh karena itu, dibutuhkan reformasi di ranah undang-undang yaitu dengan menerapkan metode omnibus untuk merancang undang-undang sapu jagat yang dapat mengintegrasikan norma-norma hukum dalam banyak undang-undang secara efektif dan efisien.